PERLINDUNGAN HUKUM BAGI PEMEGANG HAK CIPTA MOTIF BATIK BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Alif Zainal Arifin; Putri Maha Dewi; Fatma Ayu Jati Putri (Bajang Institute, 2026)
This study aims to analyze the forms of legal protection provided to copyright holders of batik motifs under Law Number 28 of 2014 concerning Copyright and to examine the effectiveness of dispute resolution through alternative dispute resolution (mediation) in providing legal protection for copyright holders of batik motifs. This research employs a normative legal research method using both a statutory approach and a conceptual approach. The data used in this study consist of secondary data derived from primary, secondary, and tertiary legal materials. Data were collected through library research and analyzed using a qualitative method. The results of the study indicate that Law Number 28 of 2014 concerning Copyright has established a comprehensive legal protection framework for batik motifs as copyrighted works with both cultural and economic value. Such protection is provided through preventive measures in the form of automatic copyright protection upon the creation of a work and copyright registration facilities that serve as important legal evidence. In addition, repressive protection is available through civil lawsuits, criminal sanctions, and out-of-court dispute resolution mechanisms. The study further finds that mediation, as regulated under Article 95 of Law Number 28 of 2014 concerning Copyright, constitutes an effective dispute resolution mechanism in protecting the rights of copyright holders of batik motifs. Mediation not only ensures legal certainty and the restoration of the creator’s economic and moral rights but also preserves harmonious relationships between the parties and supports the protection of cultural values embodied in batik motifs. Therefore, mediation serves as a dispute resolution instrument that is consistent with the principles of justice, legal certainty, and legal benefit in copyright protection for batik motifs.